Visuospatial sequence learning on the serial reaction time task modulates the P1 event‐related potential. (23rd September 2018) - Lum, Jarrad A. G.; Lammertink, Imme; Clark, Gillian M.; Fuelscher, Ian; Hyde, Christian; Enticott, Peter G.; Ullman, Michael T.
Abstract: This study examined whether the P1, N1, and P3 ERP components would be sensitive to sequence learning effects on the serial reaction time task. On this task, participants implicitly learn a visuospatial sequence. Participants in this study were 35 healthy adults. Reaction time (RT) data revealed that, at the group level, participants learned the sequence. Specifically, RT became faster following repeated exposure to the visuospatial sequence and then slowed down in a control condition. Analyses of ERP data revealed no evidence for sequence learning effects for the N1 or P3 component. However, sequence learning effects were observed for the P1 component. Mean P1 amplitude mirrored the RT data. The analyses showed that P1 amplitude significantly decreased as participants were exposed to the sequence but then significantly increased in the control condition. This suggests that visuospatial sequence learning can modulate visual attention levels. Specifically, it seems that, as sequence knowledge is acquired, fewer demands are placed on visual attention resources.